Targeted and Synergistic Codelivery of Chemotherapeutic and Nucleic Acid Drugs by Liposome-Coated MPDA Nanoparticles for Advanced Prostate Cancer Treatment - Dai, Liang; Ma, Wangteng; Song, Zixuan; Lu, Binwei; He, Yuchu; Zhang, Jidong; Wei, Dapeng; Wang, Baibing; Li, Guangming; Gao, Dawei; Wang, Yimin (ACS applied materials & interfaces, 2025)
Docetaxel (DTX)-based chemotherapy is the primary therapeutic approach for advanced prostate cancer (PCa) when endocrine therapy proves ineffective. Traditional chemotherapy exhibits poor specificity and induces severe side effects, such as immunosuppression, neurotoxicity, and hypersensitivity. In this study, we aimed to develop a new targeted nanodrug delivery system to accurately identify PCa cells and deliver drugs. We prepared mesoporous polydopamine (MPDA) nanoparticles using a one-pot method. After loading DTX onto MPDA, siRNA was attached to the surface, which was coated with polyethylene glycol lipids film (PEG-Lips); together, this formed MDS@L. The aptamer A10-3.2 was coupled to the surface of PEG-Lips to obtain MDS@LA, which was characterized using different techniques, including transmission electron microscopy and Fourier transform infrared spectroscopy. MDS@LA exhibited excellent stability, acid-responsive release, and photothermal properties, enhancing its antitumor effects. Both in vitro and in vivo experiments revealed that MDS@LA precisely targeted PCa cells and effectively delivered DTX and siRNA, leading to significant inhibition of PCa cell growth and proliferation. This versatile nanoplatform offers a promising, precise, and efficient therapeutic approach for advanced PCa, addressing the limitations of conventional chemotherapy.